Non-immune hydrops fetalis: etiology, pathogenesis, features of diagnosis and treatment in the fetus and newborn - S. V. Dumova; H. A. Sarkisyan; O. L. Chugunova; I. D. Prokhorov; M. I. Nikolaeva; M. R. Globa; D. I. Nam; I. V. Zhuravleva; P. V. Shumilov (LLC "Diagnostics and Vaccines", 2024)
Non-immune hydrops fetalis is a polyetiological disease characterized by high perinatal mortality. The development of non-immune fetal hydrops is associated with diseases of the cardiovascular and lymphatic systems, genetic and chromosomal diseases, infectious agents and many other reasons. In this regard, there is no single approach to the treatment of this extremely dangerous pathological condition, which requires the joint work of specialists from different specialties: obstetricians-gynecologists, neonatologists, cardiologists, surgeons, hematologists and geneticists. This article provides a review of current literature data on the etiology, pathogenesis, clinical manifestations, treatment and outcomes of non-immune hydrops fetalis.